YAP/Nrf2 suppresses ferroptosis to alleviate acute lung injury induced by intestinal ischemia/reperfusion - Lu Tang; Chengjie Yang; Yanhua Peng; Mudi Liu; Na Wei; Xin Fan; Bo Yang; Jing Jia; Ye Chen; Jianguo Feng; Jun Zhou (Redox Biology)
Intestinal ischemia reperfusion (II/R) injury is a common critical disease with high morbidity and mortality. The mechanism of II/R-induced acute lung injury (ALI) is not fully elucidated. Yes-associated protein (YAP), a downstream transcriptional coactivator of the Hippo signaling pathway, plays a central role in controlling organ development and cell proliferation. However, whether YAP is involved in regulating II/R-induced ALI remains to be further explored. This study aimed to investigate the regulatory role of YAP in ALI and ferroptosis caused by II/R, and to explore whether YAP exerts anti-ferroptosis and anti-inflammatory effects by promoting nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear entry and upregulating Nrf2 expression. In vivo models demonstrated that overexpression of YAP inhibited II/R-induced ALI and ferroptosis. This was evident through the upregulation of glutathione peroxidase 4 (GPX4), solute carrier family 7 member 11 (SLC7A11), and Nrf2 expression, as well as the mitigation of characteristic mitochondrial ferroptosis changes in lung type II epithelial cells. Additionally, YAP overexpression protected against II/R-induced ALI in mice, leading to notable improvements in lung pathology, reduced pulmonary edema, and decreased lung inflammation. Consistent conclusions were also reached in vitro models. It was observed that overexpression of YAP inhibited ferroptosis and oxidative stress by increasing Nrf2 expression and promoting its nuclear translocation. Additionally, it was discovered that knocking down Nrf2 resulted in the abolition of YAP-mediated ferroptosis alleviation in MLE-12 cells. Based on our findings, we can infer that YAP inhibits ferroptosis by upregulating Nrf2 expression and promoting its translocation into the nucleus, thereby ameliorating oxidative stress and lung injury along with the systemic inflammatory response following II/R. Furthermore, we propose that targeting YAP could be a promising approach for the treatment of ALI by suppressing ferroptosis.